Identification of a Five-miRNA Signature for Diagnosis of Kidney Renal Clear Cell Carcinoma - Zhao, Enyang; Li, Xuedong; You, Bosen; Wang, Jinpeng; Hou, Wenbin; Wu, Qiong (Frontiers in Genetics, 2022)
Motivation: Kidney renal clear cell carcinoma, which is a common type and accounts for 70%-80% of renal cell carcinoma, can easily lead to metastasis and even death. Reliable signature for diagnosis of this cancer is in need. Hence, we seek to select miRNAs for identifying kidney renal clear cell carcinoma. Method: A feature selection strategy is employed and improved to identify microRNAs for diagnosis of kidney renal clear cell carcinoma. Samples representing kidney renal clear cell carcinoma and normal tissues are split into training and testing group. Accumulated scores representing the variable importance of each miRNA are derived from an iteration of resampling, training and scoring. Those miRNAs with higher scores are selected based on Gaussian mixture model. Ten times of sample split are repeated in order to get more central miRNAs. Results: 611 samples are downloaded from TCGA, each of which contains 1343 miRNAs. The improved feature selection method is implemented, and five miRNAs are identified as a biomarker for dignosis of kidney renal clear cell carcinoma. GSE151419 and GSE151423 are selected as the independent testing sets. Experimental results indicate the effectiveness of the selected signature. Both data-driven measurements and knowledge-driven evidence are given to show the effectiveness of our selection results.